A proposed framework to establish in vitro-in vivo relationships using gastric digestion models for food research - Nadia J; Roy D; Montoya CA; Singh H; Acevedo-Fani A; Bornhorst GM (The Royal Society of Chemistry, 2024)
In vitro digestion methods have been utilized in food research to reduce in vivo studies. Although previous studies have related in vitro and in vivo data, there is no consensus on how to establish an in vitro-in vivo relationship (IVIVR) for food digestion. A framework that serves as a tool to evaluate the utility and limitations of in vitro approaches in simulating in vivo processes is proposed to develop IVIVRs for food digestion, with a focus on the gastric phase as the main location of food structural breakdown during digestion. The IVIVR consists of three quantitative levels (A, B, and C) and a qualitative level (D), which relate gastric digestion kinetic data on a point-to-point basis, parameters derived from gastric digestion kinetic data, in vitro gastric digestion parameters with in vivo absorption or appearance parameters, and in vitro and in vivo trends, respectively. Level A, B, and C IVIVRs can be used to statistically determine the agreement between in vitro and in vivo data. Level A and B IVIVRs can be utilized further evaluate the accuracy of the in vitro approach to mimic in vivo processes. To exemplify the utilization of this framework, case studies are provided using previously published static and dynamic gastric in vitro digestion data and in vivo animal study data. Future food digestion studies designed to establish IVIVRs should be conducted to refine and improve the current framework, and to improve in vitro digestion approaches to better mimic in vivo phenomena.
Keywords: Digestion; Humans; Models, Biological; Animals; Gastric Mucosa; Stomach; Kinetics